Respuesta :

Answer:

(-1.5,-1)

Step-by-step explanation:

To find the x coordinate of the midpoint, add the x coordinates of the endpoints and divide by 2

(-1+-2)/2 = -3/2 = -1.5

To find the y coordinate of the midpoint, add the y coordinates of the endpoints and divide by 2

(2+-4)/2 = -2/2 = -1

(-1.5,-1)

Answer:

Answer: The third objective

[tex] \hookrightarrow \: { \tt{midpoint = ( \frac{x _{1} + x _{2} }{2} , \: \frac{y _{1} + y _{2} }{2} )}} \\ [/tex]

• x1 → -1

• x2 → -2

• y2 → -4

• y1 → 2

[tex]{ \tt{midpoint = ( \frac{ - 1 + ( - 2)}{2} , \: \frac{2 + ( - 4)}{2} )}} \\ \\ { \tt{midpoint = ( \frac{ - 3}{2} , \: \frac{ - 2}{2} )}} \\ \\ { \tt{midpoint = ( - 1.5, \: - 1)}}[/tex]

ACCESS MORE